Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Porous covalent organic nanotubes and their assembly in loops and toroids - Koner, Kalipada; Karak, Shayan; Kandambeth, Sharath; Karak, Suvendu; Thomas, Neethu; Leanza, Luigi; Perego, Claudio; Pesce, Luca; Capelli, Riccardo; Moun, Monika; Bhakar, Monika; Ajithkumar, Thalasseril G.; et al. (Nature Chemistry, 2022)
Carbon nanotubes, and synthetic organic nanotubes more generally, have in recent decades been widely explored for application in electronic devices, energy storage, catalysis and biosensors. Despite noteworthy progress made in the synthesis of nanotubular architectures with well-defined lengths and diameters, purely covalently bonded organic nanotubes have remained somewhat challenging to prepare. Here we report the synthesis of covalently bonded porous organic nanotubes (CONTs) by Schiff base reaction between a tetratopic amine-functionalized triptycene and a linear dialdehyde. The spatial orientation of the functional groups promotes the growth of the framework in one dimension, and the strong covalent bonds between carbon, nitrogen and oxygen impart the resulting CONTs with high thermal and chemical stability. Upon ultrasonication, the CONTs form intertwined structures that go on to coil and form toroidal superstructures. Computational studies give some insight into the effect of the solvent in this assembly process.

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting